Gambaran kualitas tidur dan indeks prestasi siswa kelas XII SMA Negeri 1 Manado di masa pandemi COVID-19 - Iftitah M. P. Sonda; Windy M. V. Wariki; Frelly V. Kuhon (UNIVERSITAS SAM RATULANGI, 2021)
Introduction: The achievement index is a measure of student success in the learning process at school. A factor that could affect the success of students to help achieve a satisfactory index during the COVID-19 pandemic is sleep quality. Having changes in daily activities can lead young adult students to not be able to control themselves when it comes to time management. Because of this, they put aside their daily activities and this messes up their sleep schedules.Objective: Determine the overview of the sleep quality and the achievement index of students in class XII of SMA Negeri 1 Manado during the COVID-19 pandemic.Methode: The type of research that is conducted is descriptive research with a cross sectional design and proportional random sampling technique, the research instrument that is used is the Pittsburgh Sleep Quality Index (PSQI) questionnaire and data on achievement index scores from local agencies.Result: Total of 86 respondents participated in this study. Of all class XII students of SMA Negeri 1 Manado, 44.2% had good quality and 55.8% had poor sleep quality (55.8%), and had a high achievement index of 77.9% in the period before the COVID-19 pandemic. and by 100% during the COVID-19 pandemic.Conclusion: Some of class XII students have poor sleep quality and some have good sleep quality, and have a high achievement index in the period before the COVID-19 pandemic and during the COVID-19 pandemic.Key Words: sleep quality, adolescent, achievement index, COVID-19